1978
DOI: 10.1007/bf00232599
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity and fragment size of DNA from mouse TLT hepatoma chromatin and chromatin fractions using endogenous and exogenous nucleases

Abstract: The action of micrococcal nuclease, DNase I and DNase II on mouse TLT hepatoma chromatin revealing the periodicity of its structure as visualized by denaturing and non-denaturing gel electrophoresis, was consistent with the action of these enzymes on other chromatins. Micrococcal nuclease showed a complex subnucleosome fragment pattern based on multiples of 10 base pairs with a prominant couplet at 140/160 base pairs and the absence of the 80 base pair fragment. This couplet of the core and minimal nucleosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…In the light of these findings, the associated release of RNA polymerases and part of the nuclear DNA in the autodigestion technique invites speculation that the released DNA may be enriched for transcribed sequences. A preliminary report confirming this has already been published (34) and indirect evidence from other groups has suggested that hepatic endogenous nucleases may preferentially digest transcriptionally active chromatin (27,35). A more detailed analysis of the DNA sequences released in our system is in preparation.…”
Section: Discussionsupporting
confidence: 83%
“…In the light of these findings, the associated release of RNA polymerases and part of the nuclear DNA in the autodigestion technique invites speculation that the released DNA may be enriched for transcribed sequences. A preliminary report confirming this has already been published (34) and indirect evidence from other groups has suggested that hepatic endogenous nucleases may preferentially digest transcriptionally active chromatin (27,35). A more detailed analysis of the DNA sequences released in our system is in preparation.…”
Section: Discussionsupporting
confidence: 83%
“…To this end, Transplantable Liver Tumor (TLT) cells-a murine hepatocarcinoma cell line-were cultured in the absence or in the presence of tellurite and biochemical and morphological determinations were carried out in order to determine the extent and type of cell death. TLT cells have been previously used to assess both in vivo and in vitro anticancer cytotoxic effects (Duerksen and Connor 1978;Taper et al 1987;Verrax et al 2004;Crokart et al 2005;Benites et al 2008). Experimental tests included lactate dehydrogenase (LDH) leakage (cell survival), ATP levels (functional ability of cells), and caspase-3 (DEVDase) activity and cleavage of poly(ADPribose)polymerase (PARP) to assess the nature of the cell demise.…”
Section: Introductionmentioning
confidence: 99%